Colaboração no processo de produção textual em uma atividade online: um estudo de caso com o gênero resenha de filme - Monica da Cunha Melo Veado (2008)
In this study, we observed the interaction and collaboration processes among students while they produced two film reviews in an online environment. Our main aim was to understand how this collaboration could take place in an asynchronous communication environmentwhere individuals remain physically distant, as well as to analyze the impact, if any, of the proposed activities on the writing process. Also, we aimed to investigate how the new information and communication technologies may contribute to the creation of new languagelearning environments based on peer collaboration. Six advanced adult students participated in this project. They all have Portuguese as theirmother tongue and have been studying English as a foreign language in private classes for at least four years. Two blogs were created, one to present the activities prepared to assist the students when writing their reviews and the other to post their final work. A wiki page was also set up in order to allow participants to collaborate while producing their texts and a private discussion group was opened in Yahoo Groups to facilitate interaction and communication among the students as well as with the teacher/researcher. All the tools selected can be easily found free of charge on the internet and none of them require that users possess any technical knowledge to successfully work with them. The theoretical background for this case study was based on the concepts of interaction and collaborative learning, the theoretical models of the writing process, as well as the main theories involving text genres. We have also taken into consideration recent studies related to the use of new information and communication technologies in learning environments, withspecial emphasis on the use of web2.0 tools to teach and learn foreign languages. The results showed that students considered the experience very positive and that they felt comfortable working together using asynchronous tools, both in pairs and as a group. Among the main advantages of the online environment, students pointed to the flexibility of the system and the possibility of interacting and working according to their own needs and preferences. Although the number of interactions seemed to be smaller than originally anticipated, they were objective and targeted to the goals set, thus leading to the improvement of the reviews written. The main changes could be noticed at the discursive level, as well as in the adequacy of the text in relation to the genre selected and the students attention to aspects involving the target reader and place of publication. The online environment proved to be a useful and reliable alternative space for writing practice and for the interaction and collaboration in an educational setting. We believe this is a promising field for further studies, not only with a view to text production, but also focusing on different levels of student proficiency, skills, text genres and tools.